Retail Management System Training for Catering MSMEs to Support Digital Transformation - Sabril, Aulia; Nur Hasanah; Suhaeb, Sutarsi; Atmasani, Dian (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2026)
This community engagement program aimed to enhance the digital capacity of small and medium catering business owners through structured training in using a Retail Management System (RMS). The training was conducted in multiple phases, including system introduction, simulation, and real-time transaction practice. A total of 18 MSME participants were guided through practical modules such as sales input, inventory tracking, and digital receipt generation. Post-training results indicated a significant increase in participants’ confidence and efficiency, with many reducing manual recordkeeping by more than 50%. Beyond technical skills, the program fostered digital literacy and encouraged data-driven decision-making within daily operations. This initiative contributes to the digital transformation of food service MSMEs and presents a scalable model for empowering small businesses through targeted technology adoption.